Dominant firms’ shocks and earnings management - Viana, D. B. C., Jr.; Lourenço, I.; Branco, M.; Costa, F. (44th European Accounting Association Annual Congress, 2022)
This study analyzes whether dominant (extremely large) firms’ idiosyncratic shocks affect earnings management of non-dominant firms. Following relevant macroeconomic literature, shocks to dominant firms are measured by abnormal levels of sales growth, considering both country- and industry-level benchmarks – thus, the greater the shocks, the greater the abnormal sales growth. Based on a cross-country setting of firms from European Union countries, we predict and find that the level of dominant firms’ shocks is negatively associated with earnings management practices of non-dominant firms. Aligned with the granular hypothesis suggested by Gabaix (2011) seminal work, these findings suggest that positive shocks to dominant firms could positively beneficiate other firms, as well as to be related to expansion of the economy, less macroeconomic uncertainty and, hence, to discourage earnings management of non-dominant firms.